Acute jaundice as a manifestation of midgut volvulus in a 6-year-old child: A case report - Ali Alakbar Nahle; Hussein Hamdar; Dina Essayli; Rim Awada; Nafiza Martini; Mohammad Kanbar; Husam Dalati (Elsevier, 2023)
Introduction: Midgut malrotation is a congenital anomaly characterized by the incomplete rotation of the midgut during embryonic development. Although often asymptomatic, midgut malrotation can lead to complications such as midgut volvulus. Previous studies showed that extrahepatic obstructive jaundice is a rare manifestation of intestinal malrotation. Case presentation: A 6 -year-old male presented with sudden-onset jaundice, decreased appetite, and abdominal pain. Physical examination revealed severe abdominal tenderness. Laboratory tests showed elevated bilirubin levels and liver enzyme markers. Abdominal X-ray and ultrasound findings suggested intestinal malrotation with volvulus. Subsequently, an upper gastrointestinal series confirmed the diagnosis of midgut volvulus. Emergency exploratory laparotomy was performed, and the Ladd's procedure was carried out to correct the malrotation. The patient's jaundice resolved rapidly post-surgery, and he was discharged with normal laboratory results. Conclusion: This case report highlights the importance of recognizing midgut malrotation as a potential underlying cause of jaundice in children, despite its rarity.